Differential effects of combinations of anti-retrovirals and progestins on gene expression and HIV-1 replication in cells of the female genital tract - Dlamini, Sigcinile (Department of Molecular and Cell Biology, 2018)
Young women in areas of high HIV risk are more vulnerable to new HIV infections compared to men. With the development of programmes using anti-retrovirals (ARVs) to prevent HIV infection, the concurrent use of hormonal contraception and ARVs is likely to increase in young women. Products delivering ARVs and hormonal contraceptives intravaginally, are in development, and aim to simultaneously prevent unintended pregnancies and prevent HIV infection. However, little is known about the combinatorial effects of ARVs and hormonal contraceptives in the female genital tract. The mucosal surface in the female genital tract is the initial site of HIV entry and viral replication. Understanding the effect of hormonal contraceptives and ARVs is relevant to the potential safety of these for long term use. The present study aims to investigate the effects of the ARVs dapivirine (DPV), tenofovir disproxil fumarate (TDF) and a panel of progestins, alone and in combination with each other, on the expression of immune function genes relevant to HIV acquisition, on steroid receptor activity, and on HIV replication. Analysis of expression of select pro- and anti- inflammatory genes revealed that, DPV exerts gene-specific pro-inflammatory and cytotoxic effects on cervical cells and tissue. Co-stimulation with the progestin medroxyprogesterone acetate (MPA) revealed that MPA can potentiate and inhibit the DPV-induced pro-inflammatory effects, in a gene-specific manner in cervical cells. DPV was shown to alter the efficacy and potency of an androgen receptor (AR) ligand, demonstrating its ability to influence AR activity. Furthermore, DPV inhibited viral replication but also increased HIV co-receptor expression in the absence and presence of MPA. In contrast to DPV, TDF had no effect on the expression of pro-inflammatory immune function genes or HIV co-receptors in the absence and presence of MPA. TDF had no effect on endogenous steroid receptor levels in cervical cells and showed no significant effects on steroid receptor transactivation. In summary, data from the present study show that TDF may be the better choice of ARV for combinatory usage with hormonal contraceptives. An association between genital inflammation and HIV acquisition has previously been established and thus the potentiated pro-inflammatory effects of DPV may potentially change the microenvironment of the female genital tract to favour increased risk of HIV or other genital tract infections, when used alone and in combination with hormonal contraceptives such as MPA. Furthermore, DPV's influence on steroid receptor activity points towards potential for increased side effects due to off-target AR effects. These results have serious implications for women using hormonal contraception who may consider the use of DPV as a microbicide. However, whether in vitro results will occur in vivo, remains to be established.